Pembekalan Peran Talent Development Institute (TDI) Pada Fungsi Sumber Daya Manusia PT. Indako - Santosa, Sonny; Anggraeni, Tri; Elizabeth, Elizabeth; Novianti, Rini; Susanto, Susanto; Kurniawan, Ari (Abdi Dharma, 2022)
Talking about talent management, it is related to the roles and responsibilities of leaders. Based on this, it is deemed necessary to have a briefing activity that is refresher related to talent management issues, for example, the adequacy aspects related to talent management such as vision, mission and goals as well as the company's strategy to build a talent management system, the main objective of this activity is to provide briefing related to several issues that must be known in advance regarding the goals to be built from talent management itself in the company, this activity is carried out online through a webinar which is attended by the system development team at PT. Indako on February 25, 2022. The results of this briefing activity obtained an understanding that the more specific the company's vision, mission, goals and strategies are, the clearer the goals to be achieved with this talent management system, so that its contribution to organizational growth will be much more leverage and of course This will ultimately increase the productivity of the employees and increase the job satisfaction of each individual.